The Effect of Supply Chain Integration, Agility, Sustainability on Supply Chain Performance Mediated by Supply Chain Robustness and Resilience in Logistics Companies in Java Island - Anni Kholila Harahap; Iveline Anne Marie (Universitas KH. Abdul Chalim Mojokerto, 2025)
Java Island contributes 57.05% to the Indonesian economy, with the logistics sector as one of the main contributors (13.96%) through transportation and warehousing. However, this sector faces challenges in the form of high logistics costs. Logistics performance, as measured by the Logistics Performance Index (LPI), shows a downward trend in Indonesia. This study aims to analyze the influence of integration, agility, robustness, resilience, and sustainability supply chain on supply chain performance. Using a hypothesis testing approach with Structural Equation Modeling (SEM) through the AMOS program, primary data were collected from 289 logistics sector employees in Java Island using the technique of purposive sampling. The results of the study show a positive influence of supply chain integration on agility, resilience, resilience, and sustainability. Agility affects supply chain resilience and performance, while resilience also affects supply chain performance. However, there was no positive influence of resilience on resilience, resilience on performance, or integration on performance through resilience. Sustainability has the strongest influence on supply chain performance (0.834) compared to other factors. This study is limited to the logistics industry in Java Island, and it is recommended that similar studies be conducted in other sectors or regions to broaden insights. This study contributes to the supply chain literature and provides practical implications for logistics companies.